Elis, PERANCANGAN SITUS WEB MINDLAB KELAPA GADING - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2012)
One of the fast pace technology development major effects is that internet access, that is becoming more and more usual. These days the scope of internet use is very broad, ranging from international-scale business to home-made recipe search. Almost every internet user interacts with website, which can be used both as information pool also as instrument which takes input and gives information output that is useful to the user.Mindlab Kelapa Gading is an early-childhood education institution, specialized in developing childrenâ€™s thinking skills, social skills, and emotional skills through various games. This institution needs a website that provides information about learinng programs and events held by institution. The purpose of this research is to design and build a website that augments the information service toward the institutionâ€™s students and parents, also as the institutionâ€™s medium of socialization toward society. This website is divided into front end and back end. Front end consists of web pages that are accessible to general user, institutionâ€™s students, and their parents. Back end is the part of website that is accesible only to web administrators (furthermore will be shorten to â€œweb adminâ€) to manage front end content and order. The whole website is build in HTML and PHP programming language using Macromedia Dreamweaver MX 2004 as its application software. The website is connected to a database, which consists of related tables. The database is build in MySQL 5.0 language and website connection to database server is done by using phpMyAdmin. User requirements are gathered by interviewing Mindlab Kelapa Gading operational manager, teachers, and administration officer. System is designed using data flow diagram and entity relationship diagram. The website also gives reports as its output to students, parents, and intitution management. These reports are expected to empower the decision making, thus augment the quality of studentsâ€™ education and institution service. The conclusion of this research is that the website increase eficiency and effectivity of Mindlab Kelapa Gading marketing and information service to society, specifically to students and parents.